Amine- and thiol-functionalized SBA-15: Potential materials for As(V), Cr(VI) and Se(VI) removal from water. Comparative study. (April 2021) - Dobrzyńska, Joanna
Abstract: SBA-15 type materials functionalized with 3-aminopropyltriethoxysilane (APTES), N -[3-(trimethoxysilyl)propyl]-ethylenediamine (TMPED) and 3-mercaptopropyltrimethoxysilane (MPTMS) have been compared for their ability to adsorb arsenic(V), chromium(VI) and selenium(VI) oxyanions from an aqueous solution. The effects of pH and contact time on the adsorption of As(V), Cr(VI) and Se(VI) were studied. Adsorption was very fast, a maximum of 3 min was required to reach adsorption equilibrium. Under the optimal pH values the maximum static adsorption capacities were as follows: As(V)/SBA-APTES – 36 mg g −1, As(V)/SBA-TMPED – 24 mg g −1, Cr(VI)/SBA-APTES – 51 mg g −1, Cr(VI)/SBA-TMPED – 55 mg g −1, Cr(VI)/SBA-MPTMS- 55 mg g −1, Se(VI)/SBA-APTES – 79 mg g −1, Se(VI)/SBA-TMPED – 78 mg g −1, Se(VI)/SBA-MPTMS – 31 mg g −1 . XPS studies proved that adsorption of As(V), Cr(VI) and Se(VI) onto amine- and thiol-functionalized SBA-15 leads to the reduction of adsorbate and various chemical changes of sorbent functional groups. It was shown that the 0.5 mol L −1 chloride solution prevents the adsorption of As(V) and Cr(VI) onto SBA-APTES and SBA-TMPED materials, and only slightly hinders adsorption of Se(VI). Nitrate ions have a lesser influence on the adsorption of As(V), Cr(VI) and Se(VI) than chloride ions. The application of HNO3 and HCl of various concentrations do not allow to quantitatively desorb As, Se and Cr from studied sorbents. The results suggest that amine- and thiol-functionalized mesoporous silica could be used as effective adsorbents for the removal of As(V), Cr(VI) or Se(VI) from aqueous solution.